Traditionality and modernity in Romani non-folklore literature: The stereotypical motivic analysis contrasted to the structural one - Červenka, Jan (Romano džaniben, 2019)
The article follows the opposition of traditionality and modernity in the literature of the so-called Slovak Roma. The author explores texts which refer to the ancient past of the Roma (mythic proses by Margita Reiznerová, some fairy tales by Elena Lacková) as modern individual texts that construct Romani identity in a non-traditional mode. Similarly, he regards selected texts with motives from the past but relatively recent life in Romani settlements (poetry by Vlado Oláh, proses by Erika Olahová) as individual fiction with hardly any folklore influence. On the other hand, he points out texts fully representing folklore despite using very modern motives. Based on this contrast the author warns against the dominance of motivic analysis in the classification of Romani literature and he also shows one important complementary line of modern Romani literature.